PENGEMBANGAN DIORAMA BERBASIS AUGMENTED REALITY (AR) PADA MATERI METAMORFOSIS DALAM MENINGKATKAN SELF REGULATED DAN LITERASI SAINS SISWA SEKOLAH DASAR - Faizannisa, Faizannisa; Fatih, Mohamad; Oktaviani, Ragil Tri (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop a learning medium in the form of a diorama integrated with Augmented Reality (AR) technology for the topic of metamorphosis, designed to enhance third-grade elementary students’ self-regulated learning and scientific literacy. The research employed the Research and Development (R&D) method based on the ASSURE instructional design model. During the field testing phase, a One Group Pretest–Posttest Design was applied. Data were collected through interviews (prior to development), questionnaires, tests, and supporting documentation. The results of expert evaluations indicated high validity, with media expert validation reaching 92.6% and material expert validation scoring 90%, both categorized as very valid. Teacher responses were highly positive, with an eligibility rate of 94%. Furthermore, students’ questionnaire and test results showed significant improvement in both self-regulated learning and scientific literacy, with average N-gain scores of 0.4824 and 0.6460, respectively, both in the moderate improvement category. The MANOVA test (Tests of Between-Subjects Effects) revealed significance values of 0.007 for self-regulated learning and 0.003 for scientific literacy. Since both values were below the 0.05 threshold, it can be concluded that the AR-based diorama learning medium had a significant effect on both variables.